Hierarchical-porous acoustic metamaterials: A synergic approach to enhance broadband sound absorption - Zichao Guo; Zhendong Li; Kexin Zeng; Xinying Lu; Jie Ye; Zhonggang Wang (Materials & Design, 2024)
A novel design for hierarchical-porous acoustic metamaterials (HPAM) is proposed to enhance the functionality of Helmholtz-type resonators and porous materials, achieving continuous and efficient broadband sound absorption. This method can potentially eliminate absorption valley and improve the coupling strength through a synergistic energy dissipation mechanism and hybrid impedance matching behavior. Excellent sound-absorbing capability of the elaborately crafted HPAM was demonstrated analytically, numerically, and experimentally. Specifically, the results revealed an impressive average absorption coefficient of 0.77, with 73 % of the α points exceeding 0.8 across the entire test frequency range. Furthermore, the sound absorption of HPAM can be further optimized to attain ultra-broadband properties by modifying the hierarchical configuration and composite design of the porous materials. The physical mechanism is revealed through the integration of the hierarchical scaling effect and the energy-trapped mode. Numerical simulations revealed the emergence of three distinct absorption peaks at frequencies of 0.76, 1.4, and 3.6 kHz, respectively, and the effective absorption spectrum exceeded 3.4 kHz. Overall, the proposed design highlights the role of hierarchical structures and porous materials in synthesizing superior sound-absorbing properties that fully elucidate the relationship between structure and performance, and provide an avenue for potential noise-control applications.